Evaluating the effect of dexmedetomidine premedication on the quality of subarachnoid block, haemodynamics and sedation in patients undergoing lower limb surgeries: a prospective randomized controlled trial - Sharma, Sandeep; Somani, Mahesh; Chandramohan, Madhan; Raiger, Lalit Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Present study was designed to evaluate the effect of intravenous dexmedetomidine on haemodynamics, sedation and quality of spinal anaesthesia with 0.5% hyperbaric bupivacaine. Methods: Sixty ASA grade 1 and 2, 18-60 years aged patients scheduled for elective lower limb surgeries were randomly divided into two groups: Group C (Control) and Group D (Study), received intravenous normal saline 10ml and intravenous dexmedetomidine 1μg/kg in dilution of 10ml respectively over 10minutes duration, 10minutes before subarachnoid block with 2.5ml of 0.5% hyperbaric bupivacaine. The heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), quality of sensory and motor block and level of sedation were monitored intraoperatively and postoperatively. Results: The heart rate was statistically significantly decreased in group D both intraoperatively and postoperatively. Intraoperative and postoperative SBP and DBP were lower in dexmedetomidine group but clinically that was insignificant. Intraoperative Ramsay sedation scores were significantly higher in dexmedetomidine group (3.49±0.240) as compared to control group (2.51±0.249) (p<0.001) but the patients were easily arousable. The duration of sensory blockade (208.83±9.53 min vs 162.83±9.62 min), duration for 2 dermatomal regression of sensory blockade (146.5±10.013min vs 98±8.57min) and the duration for motor block regression to Modified Bromage scale 0 (167.33±10.5min vs 137.83±11.94min) were significantly prolonged in dexmedetomidine group as compared to control group. The highest level of sensory blockade was also significantly higher in dexmedetomidine group (T6.90±0.759 vs T7.60±0.621). There was no difference in the time for attaining highest level of sensory blockade, time taken for motor blockade to reach Modified Bromage Scale 3 between both the groups. Average 24hr mean VAS score was significantly lower in dexmedetomidine group (1.37±0.15 vs1.72±0.17, p<0.001). Time to first request for rescue analgesic was also significantly longer in dexmedetomidine group (mean 174.33min vs 143.5min). Average 24hour consumption of tramadol analgesic was significantly higher in control group as compared to dexmedetomidine group (391.86±111.62mg vs 279.86±80.55mg, p<0.001). Conclusions: Intravenous dexmedetomidine significantly prolongs the duration of sensory and motor block of bupivacaine spinal anaesthesia. It provides excellent sedation and analgesia. Dexmedetomidine induced decrease in heart rate, systolic/diastolic blood pressure are not clinically significant.